2011
DOI: 10.4061/2011/510398
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Incidence, Quality of Life, and Back Pain during 18-Months Treatment with Teriparatide in Greek Postmenopausal Women with Osteoporosis: Results from the European Forsteo Observational Study

Abstract: Objective. To evaluate fracture incidence, effects on health-related quality of life(QoL), back pain (BP) occurrence and treatment compliance in Greek post-menopausal osteoporotic women treated with teriparatide (TPTD) for up to 18 months, in a naturalistic setting. Methods. 301 patients provided baseline information on demographic characteristics, fracture history, osteoporosis-related medication and risk factors. During treatment, QoL and BP severity were evaluated. Results. Mean (SD) age was 69.5 (±8.5) yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
(38 reference statements)
3
12
0
1
Order By: Relevance
“…This study shows that the fracture rate decreases with the increase of the time of administration of teriparatide. This is similar to our results [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. There are three systematic reviews and meta-analysis of the impact of anti-osteoporotic drug adherence on prognosis [17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…This study shows that the fracture rate decreases with the increase of the time of administration of teriparatide. This is similar to our results [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. There are three systematic reviews and meta-analysis of the impact of anti-osteoporotic drug adherence on prognosis [17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…Study findings also showed that the total mean score of QOL among 3413 postmenopausal women was 57.89±12.8 (in the possible range of 0-174), indicating good QOL. Several earlier studies in different countries also reported good QOL among postmenopausal women [40][41][42]. However, some studies reported low QOL among menopausal women [14,43,44].…”
Section: Discussionmentioning
confidence: 87%
“…Plus de 95 % des femmes avaient eu deux ou plusieurs fractures vertébrales, en conformité avec le critère de remboursement [11]. Elles souffraient d'ostéoporose plus sévère que les femmes de la cohorte européenne complète [15,19] et de la cohorte grecque [20], sur la base du nombre de fractures antérieures, et avec moins de maladies concomitantes [15,19].…”
Section: Discussionunclassified